The Politics of Asset Confiscation Law in Indonesia - Lusia Sulastri; Bahtiyar Efendi; Gugun Gumilar (Lex Publica, 2023)
Abstract. In practice, the system and mechanism for confiscating assets resulting from criminal acts in Indonesia, which are spread across several regulations, are still not optimal; therefore, an Asset Confiscation Bill was formed. This study examines the politics of criminal law in carrying out asset confiscation in Indonesia, the mechanisms that will be used in carrying out asset confiscation in Indonesia, and crucial matters that need to be considered in regulating asset confiscation through a normative approach. The results show that the politics of criminal law in confiscating assets in Indonesia is due to the need for a system that allows the effective and efficient confiscation of proceeds and instruments of criminal acts while paying attention to the values of justice without violating individual rights. The mechanism that will be used in confiscating assets in Indonesia under the Asset Confiscation Bill is non-criminal-based asset forfeiture. Crucial things that need to be considered include the careful execution of confiscating assets, specifying certain criminal acts to be regulated by the Asset Confiscation Bill, the utilization of the proceeds of asset confiscation from crimes not only for the state but also for parties who suffered harm as a result of related crimes, the necessity to regulate compensation for good-faith third parties, the possibility of retroactive enforcement of laws, and the consideration of non-cash assets or cryptocurrencies. Abstrak. Dalam praktiknya, sistem dan mekanisme penyitaan harta kekayaan hasil tindak pidana di Indonesia yang tersebar di beberapa peraturan masih belum optimal; Oleh karena itu, dibentuk RUU Perampasan Harta Kekayaan Tindak Pidana. Kajian ini mengkaji tentang politik hukum pidana dalam melakukan penyitaan harta kekayaan pidana di Indonesia, mekanisme yang akan digunakan dalam pelaksanaan perampasan harta kekayaan pidana di Indonesia, dan hal-hal krusial yang perlu diperhatikan dalam pengaturan perampasan harta kekayaan pidana melalui pendekatan normatif. Hasil penelitian menunjukkan bahwa politik hukum pidana dalam penyitaan harta kekayaan hasil tindak pidana di Indonesia disebabkan oleh perlunya suatu sistem yang memungkinkan penyitaan hasil dan alat-alat tindak pidana berlangsung secara efektif dan efisien serta memperhatikan nilai-nilai keadilan tanpa melanggar hak individu. Mekanisme yang akan digunakan dalam penyitaan aset pidana di Indonesia berdasarkan RUU Perampasan Aset adalah perampasan aset berbasis non-kriminal. Hal krusial yang perlu diperhatikan antara lain penyitaan harta kekayaan hasil tindak pidana yang harus dilakukan secara hati-hati; RUU Perampasan Harta Kekayaan harus mengatur tindak pidana tertentu; hasil perampasan harta kekayaan dari tindak pidana tidak hanya digunakan untuk negara tetapi juga untuk pihak-pihak yang dirugikan akibat tindak pidana yang bersangkutan; perlu diatur ganti kerugian bagi pihak ketiga yang beritikad baik; kemungkinan penegakan hukum yang berlaku surut; dan kemungkinan aset non tunai atau mata uang kripto. Kata kunci: Politik hukum, Pencucian uang, Perampasan aset, Korupsi, Indonesia